Kitchen Set Pola Penataan Dan Perawatannya Pada Rumah Tinggal - Joko Budiwiyanto (Ornamen, 2006)
Human life style being practical completely, hygienic and efficient have an effect on to room as place have activity, especially kitchen room. Present day kitchen design raced by a technological progress have succeeded to make the kitchen form look like the clinic laboratory with the electric all supply, practical, organizational and healthy consecutively. This result kitchen design tend to the people mention it with the modern kitchen term. Especial principle which must be paid attention in arranging kitchen is arranging activity sequence which is often referred with the term â€œ trilateral activity patternâ€. This trilateral activity pattern represent the distance which must be gone through by user between sinks, stove and refrigerator, representing critical shares in the plan kitchen. Arrange the sequence work to have an effect on to model of kitchen settlement. Desainers divide the kitchen model become 5 model, that is model U, Model L, parallel of wall model, the parallel model, and kitchen of the island model. Other factor which must be paid attention in arranging kitchen is treatment factor. Take care of the kitchen require to pay attention the followings, human factor being, factor of material and equipments factor. The factors have an effect on to durabel level of kitchen. In writing this article, writer try to analyse the problems which emerge in kitchen settlement and try to look for its resolving relied only by book study.Key word: Kitchen set, tata urutan kerja, sirkulasi, model dapur, perawatan